THE INFLUENCE OF NUMBERED HEAD TOGETHER WITH INTERACTIVE MULTIMEDIA ASSISTANCE OF GCD MATERIALS ON LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS - Khairun Nisa; Jesi Alexander Alim; Neni Hermita (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
Students at SDN 164 Pekanbaru who get therapy with the Numbered Head Together (NHT) cooperation model employing interactive multimedia on FPB content and students who only receive treatment with traditional learning are the subjects of this quantitative experimental research. This study used the experimental and control classes as research samples. Using the Numbered Head Together (NHT) cooperation paradigm and interactive multimedia, each class will be given a pre-test before therapy and a post-test after treatment. According to our findings, the Numbered Head Together (NHT) collaboration model, helped by interactive multimedia FPB material, had a significant impact on the learning motivation of fourth-grade children at SDN 164 Pekanbaru, as measured by pretest and posttest results of 94.03% and 109.41%, respectively, for the experimental class, whereas the control class received an averge score of 94.03% and a posttest score of 87.53%. The results show that the NHT cooperation model and interactive multimedia FPB material have an impact on the learning motivation of fourth grade students at SDN 164 Pekanbaru, with an average motivation of the experimental class being stronger than that of the control class.